Approach to management by processes in a sports department of a local government organization - Sobreiro,Pedro Alexandre (2018)
The strategy creates assumptions that should reflect the organization and the surrounding environment. The difficulties in the operationalization of the strategy and the lack of resources for the nonprofit sports organization require effective approaches. This study uses the Business Process Management to support the strategy operationalization using improvement actions according to the existing circumstances of each organization. Based on the action research we analyze the existing situation of nonprofit sports organizations and identify the line of actions to achieve the municipality intended outcomes. The lack of financial resources requires the identification of improvements according to the existing resources. The assessment of the concerns and issues related to stakeholders provides a mechanism to clarify which improvement action should be developed considering the involvement of different board members of the organization. The manager training in nonprofit organizations is an important area to target actions to contribute to the development of the nonprofit organizations, increasing their knowledge. Our findings highlight how the proposed approach can be used in nonprofit sports organization to develop an action plan to engage their business objectives according to its environment.